Localized Versus Generalized Granuloma Annulare: A Retrospective Review of 407 Patients. Issue 4 (July 2021) - Yousaf, Ahmed; Boustany, Osama J.; Gerbo, Michael; Waris, Shanawar; Davis, Stephen; Fang, Wei; Powers, Roxann
Background: Granuloma annulare has been linked to diabetes, dyslipidemia, thyroid disease, collagen vascular disease, malignancies, infectious hepatitis, and systemic infections. However, these associations have not been systematically investigated when categorized by its clinical variants. Objective: To evaluate disease associations of localized and generalized granuloma annulare. Methods: In total, 407 granuloma annulare patients from 1989 to 2019 were retrospectively reviewed, categorized by clinical variant (localized or generalized), age (pediatric or adult), and diagnostic method (clinical or histologic). Descriptive statistical analyses and multivariate logistic regression analysis were performed. Fisher's exact tests were conducted to produce unbiased probability values. Results: Overall, 75.2% of the study sample was female, 47.2% had dyslipidemia, 24.8% were diabetic, and 24.6% had thyroid disease. Dyslipidemia (OR 2.15, CI 1.95-2.35, P < .001), diabetes (OR 1.16, CI 1.01-1.31, P = .041), and histologic diagnosis (OR 2.08, CI 1.21-3.52, P = .007) were associated with increased risk of GGA compared to LGA. When stratified by adult versus pediatric cases, dyslipidemia and diagnostic method remained significant, but diabetes did not. Conclusions: Evaluating granuloma annulare by its clinical variants may help to determine disease associations with each variant.